An algorithm based on a possibility measure and used to evaluate the job satisfaction index - Gardashova, Latafat Abbas (Eastern-European Journal of Enterprise Technologies, 2016)
Job satisfaction has been a popular topic in research for many decades. The interest in this variable has spanned academic fields that have been broached by psychologists, management, and, more recently, economists. The present study is devoted to evaluating overall job satisfaction by using a fuzzy aggregation and a possibility measure. Many studies have been published in the area of evaluating job satisfaction. However, their methods are insufficient as they are based only on a statistical method. Therefore, perceptual data rather than numbers have been specified in this study concerning the essentials and the basic factors of job satisfaction, including such parameters as activity, independence, variety, status, supervision-human resource, supervision-technical, moral values, security, social service, authority, ability, company policies and practices, compensation, advancement, responsibility, creativity, working conditions, co-workers, recognition, and achievement. It has been proven that information determined by perception can be processed by a more adequate method, e. g., by using a fuzzy logic theory and a possibility measure.